Digital hypertension management: clinical and cost outcomes of a pilot implementation of the OMRON hypertension management platform - Holmstrand, Ericka C.; Sato, Hironori; Li, Jim; Mukherjee, Abhishek; Fitzpatrick, Nicole E.; Rayl, Kenneth R.; Colangelo, Francis R. (Frontiers in Digital Health, 2023)
Importance Home monitoring of blood pressure (BP) in hypertensive patients can improve outcomes, but challenges to both patient compliance and the effective transmission of home BP readings to physicians can limit the extent to which physicians can use this information to improve care. The OMRON Hypertension Management Platform (OMRON HMP) pairs a home BP cuff with a digital product that tracks data, provides reminders to improve patient compliance, and provides a streamlined source of information to physicians. Objective The primary objective of the quality improvement (QI) project was to test the hypothesis that use of the OMRON HMP could reduce the number and cost of hypertension related claims, relative to a retrospectively matched cohort of insured members. A secondary objective was to demonstrate improvement in control of BP among patients. Design Eligible members were recruited to the QI project between December 1, 2018 and December 30, 2020 and data collected for six months following recruitment. All members received the OMRON HMP intervention. Setting Enrollment and data collection were coordinated on-site at selected PCP partner providers in Western Pennsylvania. Eligible members were identified from insurance claims data as those receiving care for primary hypertension from participating primary care physicians and/or cardiologists. Participants Eligible members were between the ages of 35 and 85, with a diagnosis of primary hypertension. The retrospective cohort was selected from electronic medical records of Highmark-insured patients with hypertension who received care at Allegheny Health Network (AHN), a subsidiary of Highmark Health. Members were matched on baseline BP and lipid measures, age, smoking status, diabetes status, race and sex. Intervention Daily home BP readings were recorded by the OMRON HMP app. Patient data was reviewed by clinical staff on a weekly basis and treatment plans could be adjusted in response to this data. Results OMRON HMP users showed a significant increase in the number and cost of hypertension-related claims, contrary to the hypothesis, but did display improvements in control of BP. Conclusions and Relevance The use of a digital platform to facilitate at-home BP monitoring appeared to improve BP control but led to increased hypertension-related costs in the short-term.